ENDOPHYTES RHIZOBIA BACTERIA, ISOLATED FROM ACACIA MANGIUM, ITS POTENSIAL TO SUPPORT THE GROWTH OF SOYBEAN. - Sukiman, Harmastini (Teknologi Indonesia, 2015)
Acacia mangium is a legume tree species which has high tolerance with many different conditions and dry area. Aim of this research is to study the possibility of cross inoculation of rhizobium endophytic bacteria isolated from Acacia mangium to soybean plant and to find out the best combination of inoculants to develop biofertilizers quality. Isolation of rhizobium endophytes from Acacia mangium analysed using 16S rRNA methods identified that the bacteria belonged to Rhizobia tropici. Results showed that single inoculation of endophytic bacteria can produce soybean seed up to 19.71 gram which was slightly higher compared with control plants of 16.0 gram and chemical fertilizer treatment plants of 18.0 gram per plant. Meanwhile, Rhizobium inoculation still gave the best production of soybean; that is 28 gram per plant. Moreover, stress test results showed that the bacteria could adapt better with acidity and salinity, including UV exposure and cold condition, yet were unable to adapt with hightemperature and oxidative condition.